Prescribing patterns of encounters in fourteen general practice clinics in rural Beijing: a cross-sectional study - Guanghui Jin; Chao Chen; Yanli Liu; Yali Zhao; Lifen Chen; Juan Du; Xiaoqin Lu; Jianjun Chen (BMC, 2019)
Abstract Background General practice clinics are the main primary care institutions providing ambulatory care in the rural areas of Beijing, rational use of medicines is crucial for the rural primary care system. This study investigated the prescribing patterns of general practice clinics in rural Beijing to provide a baseline for monitoring and promoting the rational use of medicines. Methods We performed a cross-sectional study at 14 rural community health service centers in 6 non-central districts of Beijing sampled through a multistage approach, 85 general practitioners were selected from the 14 centers. Total 8500 prescriptions were derived by recording 100 consecutive patients of each the general practitioner. The World Health Organization drug use indicators and an additional indicator were adopted to assess the prescribing patterns. Results The median number of medicines per encounter was 2.0 (1.0, 2.0); the percentage of generics and essential medicines prescribed were 97.0 and 58.2%, respectively; the percentage of encounters with antibiotics prescribed was 15.1%; the percentage of encounters with injections prescribed was 3.7%; the percentage of encounters with traditional Chinese patent medicines prescribed was 52.5%; the median duration of consultation time was 6.0 (4.0, 10.0) minutes. The most frequently prescribed medicine was aspirin (low dose, 4.6%). The prescribing indicators were influenced by different patient characteristics, patients with new cooperative rural medical scheme were less likely to be prescribed with ≥3 medicines (OR 0.865), essential medicines (OR 0.812) and traditional Chinese patent medicines (OR 0.631), but were more likely to be prescribed with injections (OR 1.551) in the encounter. Patients with ≥3 problems were more likely to be prescribed with ≥3 medicines (OR 6.753), antibiotics (OR 2.875) and traditional Chinese patent medicines (OR 2.926) in the encounter. Conclusions Most indicators in this study showed similar or fair performance in comparison with World Health Organization and domestic reports, except the percentage of medicines prescribed from the essential medicine list. Regular monitoring on the prescription quality of general practice clinics in rural Beijing should be maintained.